Effect of nonmagnetic PbO nanoparticles addition on the microstructure and electrical transport properties of YBa2Cu3O7 - Keong, Stephanie Wei San (2016)
Superconductors are materials that show zero resistance when subjected to temperature under its critical temperature. Yttrium Barium Copper Oxide (YBCO) was prepared using solid state reaction method by grinding, sintering and finally pressing the samples into pellets. The objective of the research ws to study the change in (i) microstructure and (ii) electrical transport properties of YBCO with the addition of 0.00 wt%, 0.01 wt%, 0.02 wt%, 0.03 wt% and 0.04 wt% nonmagnetic PbO nanoparticles, as well as to develop a laboratory scale method in determining the electrical properties of YBCO at liquid nitrogen temperature. The presence of superconductivity was tested and confirmed when the samples was allowed to levitate above a row of Neodymium magnet and the sample with 0.04 wt% PbO nanoparticle showed the longest levitation time. From the results obtained from the X-ray diffraction, it was noted that there was minimal changes to the microstructure and composition of the superconductor when the PbO nanoparticle was added to them. A four point probe was developed to test the critical temperature of the YBCO superconductor. The results obtained does not fulfil the expected results as the critical temperature obtained for the added sample is lower than that of the referenced results which is 90 K.